2022
DOI: 10.3390/ijerph19073875
|View full text |Cite
|
Sign up to set email alerts
|

User Perception of New E-Health Challenges: Implications for the Care Process

Abstract: Establishing new models of health care and new forms of professional health-patient communication are lines of development in the field of health care. The onset of the COVID-19 pandemic has accelerated the evolution of information systems and communication platforms to guarantee continuity of care and compliance with social distancing measures. Our objective in this article was, firstly, to know the expectations of patients treated in the healthcare processes “cervical cancer” and “pregnancy, childbirth and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, this must be preceded by one or more descriptions of the effects of this digitalization, which may be harmful depending on the economic, cultural, and health contexts. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this must be preceded by one or more descriptions of the effects of this digitalization, which may be harmful depending on the economic, cultural, and health contexts. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to fewer consultations in the health and social promotion centers that use an ECR. [ 22 ] In addition, to limit waiting time, some patients may prefer to avoid going there and practice self-medication, which is becoming more and more of a public health problem. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…eHealth has been known for the past two decades and continuously evolves [7], compromising many tested methods and emerging new technologies [8]. During the COVID-19 pandemic, it was shown that some eHealth interventions, such as phone and video consultations could be implemented relatively quickly in the hospital setting [9][10][11], and many health authorities, including the Danish health authorities, now have increased focus on innovation and research based on eHealth that can be used in the healthcare setting to increase patient quality of life while taking some of the burdens off hospitals [12][13][14]. Some eHealth solutions are already implemented in hospitals, for example, electronic health records and, to some extent, online video consultation.…”
Section: Introductionmentioning
confidence: 99%